The transition from the passive to active continental margin: A case study of brittle fractures in the Miocene Loshui Sandstone on the Hengchun Peninsula, southern Taiwan. Issue 1 (26th February 2013) - Shan, Yehua; Nie, Guanjun; Yan, Yi; Huang, Chi‐Yue
Abstract : [1] In the Hengchun Peninsula, southern Taiwan, the Miocene Loshui Sandstone of deep‐sea fan facies provides an opportunity and challenge to investigate the brittle deformation history of an emerging accretionary prism. A survey of brittle fractures was carried out along the coastline. The brittle fractures include joints of various sets, a few faults and veins. The intricacy of joints lies in the large number of joint sets that often vary not only from one site to another site but in bed thickness at a given site as well and in the complicated abutting relationships between the joint sets. In order to investigate the joint sequence, we define a full spectrum of possible systematic joint sets and develop an algorithm to determine the shortest joint sequence from the observed abutting relationships. Little difference between the shortest joint sequences for the southern and northern parts of the study transect attests to the evolution of overall uniform stress throughout the area that is responsible for these various systematic newly formed or reactivated joint sets. The fracture sequence derived reveals a complicated stress evolution during the transition from the passive to active continental margin. Key Points: Brittle fractures include dominantly various joints, and faults and veins The evolution of overall uniform stress A complicated brittle deformation history during marginal transition